BRODUT: Adaptasi Musik Dangdut dalam Kesenian Kubro Siswo di Dusun Gunung Lemah Kabupaten Magelang - Aditya, Bonggan; Muttaqin, Mohammad (Dinasti Research, 2025)
This research examines the phenomenon of dangdut music adaptation within the traditional art form of Kubro Siswo in Gunung Lemah Hamlet, Magelang Regency, now known as